2023
DOI: 10.1007/s11468-023-01837-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Goos-Hänchen Shift of SPR Sensor with TMDCs and Doped PANI/Chitosan Composites for Heavy Metal Ions Detection in Aquatic Environment

Abstract: A novel surface plasmon resonance (SPR) sensor with transition metal dichalcogenides (TMDCs) and polyaniline (PANI)/chitosan composite for detection of heavy metal ions in an aquatic environment is proposed and analyzed. The Goos-Hänchen (GH) shift is employed as an important method for analyzing the performance of the SPR sensor. It is theoretically shown that the GH shift can be signi cantly enhanced in the SPR structure silver (Ag) coated with a TMDCs and PANI/CS heterostructure. When the incident light wav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…This shift serves as an apt detection signal, unaffected by variations in light source intensity [19]. Since its experimental discovery in 1947, GHS has spurred numerous theoretical and empirical studies and has found applications in sensors [20][21][22], optical switches [23,24], and optical storage [25]. Notably, with GHS's tight association with the electromagnetic properties of materials (like refractive index), it is emerging as a detection method in chemical and environmental realms [26,27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This shift serves as an apt detection signal, unaffected by variations in light source intensity [19]. Since its experimental discovery in 1947, GHS has spurred numerous theoretical and empirical studies and has found applications in sensors [20][21][22], optical switches [23,24], and optical storage [25]. Notably, with GHS's tight association with the electromagnetic properties of materials (like refractive index), it is emerging as a detection method in chemical and environmental realms [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, with GHS's tight association with the electromagnetic properties of materials (like refractive index), it is emerging as a detection method in chemical and environmental realms [26,27]. Recent research by Min Jin in 2023, for instance, leveraged a specifically designed GHS sensor for detecting aquatic heavy metal ions [20]. Jiangyu Liu explored the feasibility of using a designed terahertz GHS sensor for detecting biological small molecules [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation